An assessment of the farm improvement programme (Reg. 797/85) in the West of Ireland - Anthony Leavy; Patrick Commins; Perpetua McDonagh (European Regional Science Association (ERSA), 1998)
The Farm Improvement Programme (FIP) (Reg. 797/85) was introduced in Ireland in 1986 to replace the Farm Modernisation Scheme (FMS) (Dir. 159/92) of 1974-1985. Both schemes had similar objectives. Participants in each followed a grant aided farm development plan drawn up and operated in conjunction with their farm adviser. Nearly three quarters of farmers participated in either the FIP or FMS. This study was carried out on a sample of 145 FIP participant farms. The objective was to assess the impact of the measure on regional resource use. The average size of the farm business, as measured by standard gross margin, expanded by 15 per cent over the period of the plan. This compared with a planned increase of 9 per cent. Two-thirds of participants expanded the size of their businesses. Some outperformed their gross margin targets to a considerable extent. One-third of farms suffered a decline in gross margins. Stocking rate increased by 9 per cent from 1.38 to 1.5 livestock units per ha and the productivity of labour increased by 37 per cent. The internal rate of return to all resources involved (including farm investment, grant aid, administration and advisory costs) was high. Eighty to ninety per cent of the on farm development work was carried out by local labour. While sixty two per cent of applicants reported that they would not have made any investments without the aid of the scheme, 26 per cent said that they would have gone ahead in its absence. The conclusions from the study are as follows: Compared to the rest of Europe Irish agriculture is extensive and under capitalised with a high level of underutilisation of resources. It should therefore be a priority to increase the contribution of agricultural resources to rural and national development by improving their productivity. Because of the high and widespread participation of farmers in both schemes and the positive outcomes on the majority of participant farms, the FIP/FMS programmes seem to provide a suitable model for such development.
Keywords: 330